State and Prospects of Solar Energy Development - Petrushka, Kateryna; Hanuliak, Julianna; Petrushka, Ihor (Видавництво Львівської політехніки, 2022)
The potential of solar energy in Ukraine is high enough for widespread implementation. The most promising method of obtaining electricity is a method of direct conversion of radiation into electricity using solar panels. The production of electricity using solar panels prevents air pollution compared to the production of electricity by thermal power plants and reduces greenhouse gas emissions. The conversion of solar energy into electricity is environmentally friendly compared to traditional energy sources, but at the same time, after their operation, they generate waste that is difficult to utilize.
Keywords: renewable energy sources; solar energy; solar power plant; photovoltaic plant